The Survey of Food Consumption Among Traders with Hypertension at Bantul Traditional Market - Ririn Wahyu Hidayati (Universitas 'Aisyiyah Yogyakarta, 2020)
Hypertension is a non-communicable disease which ranks in the top 3. Untreated hypertension will have an impact on increasing the incidence of stroke and coronary heart disease. The prevalence of hypertension in Indonesia is 25, 8%, while the incidenceof hypertension in Special Region of Yogyakarta is 25,7%. In Indonesia in 2017, 77% of people with a history of hypertension had a stroke. Therefore, in 2025 it is projected that 29% of the world's population or as many as 1.56 billion adults will experience hypertension. This is influenced by several factors, one of which is an unhealthy lifestyle. Efforts that have been made by Indonesia in the prevention and control of hypertension with